ANALYSIS OF THE STATE OF THE PROBLEM OF DECISION-MAKING IN THE SYSTEM OF TRANSPORT LOGISTICS IN THE DOMESTIC LITERATURE - CHYZHMOTRIA, Oleksii; VAKALIUK, Tetiana (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The problem of decision-making in the transport logistics system is one of the first places. In particular, in transport logistics, there is a problem of drawing up an optimal route to reduce time, financial, and other transportation costs. In addition, given the current problems associated with the full-scale invasion of Ukraine by Russian troops, the issue of transport logistics is becoming increasingly important. As a result, interest in this problem is growing in the scientific community. The aim of the work is a detailed study of the state of the problem of decision-making in the system of transport logistics in the domestic literature. This paper analyzes the state of the problem of decision-making in the transport logistics system in the domestic literature. It is established that there is no single approach to this issue. Some researchers consider the use of integrated indicators in determining the optimal batches of supply of goods, others consider technological solutions that are monitored through the principles and provisions for the implementation of the concept of single information space in the transport and logistics market. In addition, researchers are considering the problem of using a decision support system to select the best of all possible options for the delivery of goods to a particular group of consumers in terms of management. Some scholars consider the problems of forming approaches to the intellectualization of transport logistics modeling, others study the methods and models of transport logistics, but only in retail outlets, and some of them consider the problem of developing a decision support system for managing transportation in uncertainty. Some authors offer their methodology to minimize the total transport costs, which is to estimate the rational number of intermediate centers, as well as finding their location, and the author’s methodology for solving problems of a particular type (transport) with vague parameters. Thus, the problem of decision-making in the transport logistics system is a very important issue and requires further research for specific tasks.